The Effect of Implementing Practicum-Based Contextual Teaching and Learning Models to Improve Learning Outcomes on the Subject of Colloids - Anna Juniar; Chatrine Monalisa Br Tarigan (UNIB Press, 2024)
This research aimed to (1) know the influence of implementing the practicum-based CTL model in learning on the cognitive learning outcomes of students studying colloids in class XI SMA Swasta Bersama Berastagi (2) determine the correlation between affective scores and student learning outcomes in the application of the CTL model based on colloid subject matter practicum for class XI SMA Swasta Bersama Berastagi; (3) determine the correlation between psychomotor scores and student learning outcomes in the application of the CTL model based on colloid subject matter practicum for class XI SMA Swasta Bersama Berastagi. The research used a pretest-posttest control group design. Based on research that has been carried out, the average score obtained by experimental class students in the initial test (pretest) was 59 and the final test (posttest) was 86.13. The average score of experimental class students at the beginning (pretest) was 53.92 and the final test (posttest) was 75.25. Student learning outcomes using learning models Contextual Teaching and Learning Practicum Based experienced an increase of 67% in the medium category. This increase can be proven by the results of the hypothesis test which obtained tcount > ttable, namely 5.58 > 1.72, which proves that student learning outcomes by applying the CTL model based on class XI colloid practicum subject matter are not the same as student learning outcomes who apply the conventional model.